High Speed Data Backup and Disaster Recovery for Big Data Enterprises - M R, Jayaram; R, Ani; Narayanan, Sudheesh; Ray, Sayantan (International Journal of Engineering and Technology, 2018)
Big data is growing every second without any barriers. The exponential growth rate in the number of devices connected adds the demand for handling of large volumes of structured and unstructured data faster from these devices. Behind all of these is Big Data sitting strong in an authoritative position. Big Data has become more important in nature, as it grows in volume without any bars and also operates in click stream, IoT sensors and web or video content. In this case, obviously the plans used for traditional disaster recovery is outdated and are no longer applicable. As we have found this, it is an important measure to analyze and implement a quick disaster recovery plan that can act as a shield during cyber-attacks, natural disasters or equipment failures. The proposed system initiates protection of big data environment considering new technologies that will keep improving with growth in data, scaling, strong security and compression as well to make sure the critical data is safe and secure from simple and catastrophic equipment failures.